Effect of bacterial inoculants application and seeding rate on common vetch-oat silage quality - Marković Jordan; Blagojević Milomir; Kostić Ivica; Vasić Tanja; Anđelković Snežana; Petrović Mirjana; Štrbanović Ratibor (Biotechnology in Animal Husbandry, 2018)
The experiment was carried out to evaluate the possibility of ensiling common vetch - oat mixtures sown at five different seeding rates. Two effects were studied: seeding rate of common vetch and oat in the mixtures and application of bacterial inoculant. The pH, DM (Dry Matter) content, ammonia nitrogen, soluble nitrogen, lactic, acetic and butyric acids were determined on silages. DLG method was utilized for classification the silage quality. Common vetch and oat were grown in binary mixtures at the experimental field of the Institute for forage crops, Kruševac - Serbia, and were tested at five different mixture rates: pure vetch, 25% vetch + 75% oat, 50% vetch + 50% oat, 75% vetch + 25% oat and pure oat. Application of bacterial inoculant affected higher content of ammonia nitrogen and acetic acid (P< 0.05), but lower content of soluble nitrogen (P< 0.05). Depending on the seeding rates of common vetch and oat, 75 : 25 common vetch - oat silage had the highest content of lactic acid and the lowest content of butyric acid. Contents of DM, pH and ammonia nitrogen were similar in all silages ranged from 307.2 to 318.5 g kg-1 , from 4.27 to 4.54 and from 16.1 to 19.1% ΣN, respectively. According to the DLG method for silage quality evaluation, similar quality grades were founded.